Role of Vilici in the area of current Bosnia and Herzegovina - Imamović, Mersiha (Historical Thought, 2025)
Title of vilicus was widely spread in Roman state. It was given to slaves and freed slaves in charge of many different jobs. What was the role of vilici in the area of current Bosnia and Herzegovina, what was their status, who did they belong to, these are the questions this paper is covering. Monuments where vilici are mentioned have been found in northeastern Bosnia, which clearly proves that they were directly connected to mining activities.